PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, FINANCIAL LEVERAGE DAN LIKUIDITAS TERHADAP PERATAAN LABA - Endarwati Endarwati (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2020)
This study aims to analyse and examine empirically the factors that affect income smoothing practice among manufacturing companies listed on the indonesia Stock Exchange. Factors tested in this study are, profitability, firm size, financial leverage and Likuidity.Data collection used a purposive sampling method conducted on manufacturing companies listed on the Indonesia Stock Exchange in the period 2008 – 2013. The hypothesis were tested using Logistic regressions to examined the influence of profitability, firm size, financial leverage and Likuidity toward income smoothing practice.The result of this study showed that profitability, has significant influence to income smoothing but firm size and financial leverage hasnot significant influence to income smoothing. The tests are based on confidence level of 95% and the error rate 5%.